2021
DOI: 10.3389/fneur.2021.656349
|View full text |Cite
|
Sign up to set email alerts
|

Altered Metabolites in the Occipital Lobe in Migraine Without Aura During the Attack and the Interictal Period

Abstract: Background: Although there have been many magnetic resonance spectroscopy (MRS) studies of migraine, few have focused on migraines during an attack. Here, we aimed to assess metabolite changes in the brain of patients with migraine, both during an attack and in the interictal phase.Methods: Six patients (one man and five women, mean age: 39 ± 10 years) with migraine without aura during the attack (MWoA-DA), 13 patients (three men and 10 women, mean age: 31 ± 9 years) with migraine without aura during the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The occipital cortex was the hub for visual perception and processing, and the temporo-occipital cortex also had complex functional connections including multisensory integration responsible for visual, auditory, and tactile information [39,40]. The indicator of occipital activity and neural synchronous were lower in migraine patients, and were generally thought to be associated with visual aura [41,42]. We also observed functional changes in the occipital cortex in young women with migraine without aura.…”
Section: Characteristics Of Changes Of Brain Spontaneous Activity And...mentioning
confidence: 57%
“…The occipital cortex was the hub for visual perception and processing, and the temporo-occipital cortex also had complex functional connections including multisensory integration responsible for visual, auditory, and tactile information [39,40]. The indicator of occipital activity and neural synchronous were lower in migraine patients, and were generally thought to be associated with visual aura [41,42]. We also observed functional changes in the occipital cortex in young women with migraine without aura.…”
Section: Characteristics Of Changes Of Brain Spontaneous Activity And...mentioning
confidence: 57%
“…The occipital cortex was the hub for visual perception and processing, and the temporo-occipital cortex also had complex functional connections including multisensory integration responsible for visual, auditory, and tactile information [23,24]. The indicator of occipital activity and neural synchronous were lower in migraine patients, and were generally thought to be associated with visual aura [25,26]. We also observed functional changes in the occipital cortex in young women with migraine without aura.…”
Section: Discussionmentioning
confidence: 69%
“…The Cho/Cr PMR was increased in our study. Previous studies have shown inconsistent results; no change in occipital lobe [11], decrease [74], increase in the occipital lobe [69]. It is difficult to compare these studies due to the small number of cases and/or the different clinical phenotypes.…”
Section: Magnetic Resonance Spectroscopic Examination (Mrs)mentioning
confidence: 95%